Aplikasi Quizizz Sebagai Media Pembelajaran Pendidikan Agama Islam (PAI) - Munawaroh, Faikhatul; Muhammada, Muhammada; Yusuf, Achmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Abstract: All information about the formatting requirements is contained Educators must have a lot of creative and innovative ideas in creating interesting and fun learning. Selection of appropriate learning media is one of the important things to support the success of education. The quizizz application is an interactive learning media that implements a